Optimalisasi Digital Marketing pada Kedai 57 Melalui Media Sosial Intagram dan TikTok - Hosea Ali Gothe Dewangga; Marchel Valdy; Ikmal Yasra; Allif Zidna Rosyadi; Roisul Umam; Susanto, Annie (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
In this digital era, MSME players should utilize digital media as a marketing strategy for their products so that consumers become more familiar with the products produced by these MSMEs. This community service activity aims to help Kedai 57 which operates in the food and beverage sector in optimizing digital marketing through social media Instagram and TikTok as well as digital media Google Maps, Google Site and Email Business as marketing tools and QRIS to facilitate transactions at Kedai 57 . This activity is carried out by creating Instagram and TikTok social media accounts, planning and creating content, as well as training in using social media as well as developing digital media Google Maps, Google Site, and Email Business and QRIS. The results of this activity show that there has been an increase in the average daily income generated by Kedai 57. The increase in average daily income can be seen from the average daily income in April 2024 before community service and the average daily income in May and June 2024 when community service is carried out. This community service activity has provided assistance to Kedai 57 in developing its business and provided knowledge and understanding of implementing digitalization for MSMEs in general and digital marketing in particular.